The secular and the divine in T. S. Eliot’s Ash-Wednesday and John Donne’s Devotions - Palka, Ewa (Estudios Ingleses de la Universidad Complutense, 2005)
The aim of this paper is to explore the meaning of the secular experience within the religious context in T. S. Eliot’s Ash-Wednesday and John Donne’s Devotions, drawing on a shared metaphysical dialectics. A parallelism can be traced between the progress of John Donne’s illness reflected in the meditative structure of his Devotions, and accompanied by despair and the confrontation of waste and hope, and the different sections of Ash-Wednesday which attest to resignation tainted by a pattern of birth and dying. While conceiving their experience through similar images, T. S. Eliot’s search for God mirrors John Donne’s search for the Physician. In Ash-Wednesday, the speaker’s weakness seems to be transformed through the interaction of the secular and divine love. He absolutizes woman, and overcomes spiritual dejection by contemplating nature. The search of God and man’s conscious “turning away” from Him create both desire and acceptance, an intense self-scrutiny, and the intermingling of spirituality and sensuality.